Perkembangan dan Tren E-Commerce di Indonesia - Mira Yuli; Siti Aisah (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
The development of information and communication technology is driving the growth of e-commerce in indonesia. indonesia is an archipelagic country with a large population and high internet usage rates, potentially leveraging e-commerce for modern trade, providing convenience and easy payment systems. This study aims to examine the development and trends of e-commerce in indonesia from the early 1990 as to the digitalization and fintech era. The method used is literature study by analyzing relevant sources such as journals, books, reports,and articles. The results show that the developmentof e-commerce in indonesia has gone through four phases: beginning (1990-2000), growth (2001-2006), evolution and market penetration (2007-2020), and the digitalization and fintech era (2021- present). Each phase is marked by the emergence of platforms such as Bhineka.com, Tokobagus, Tokopedia, Gojek, Bukalapak, Lazada, Shopeeand the expansion of TikTok Shop, which strengthen the digital e-commerce ecosystem and the development of payment systems such as e –wallet. This research confirms that e-commerce plays an important role in driving economic growth, expanding the UMKM market, and can increase indonesia’s competitiveness in the global digital economy era.